127k views
2 votes
Which equation is an identity?

3(x – 1) = x + 2(x + 1) + 1
x – 4(x + 1) = –3(x + 1) + 1
2x + 3 = 2 x plus 3 equals StartFraction one-half EndFraction left-parenthesis 4 x plus 2 right-parenthesis plus 2.(4x + 2) + 2
StartFraction one-third EndFraction left-parenthesis 6 x minus 3 right-parenthesis equals 3 left-parenthesis x plus 1 right-parenthesis minus x minus 2.(6x – 3) = 3(x + 1) – x – 2

User Rosalba
by
5.7k points

1 Answer

6 votes

Answer:

2x + 3 = 1/2(4x+2)+2

Step-by-step explanation: on edge

User Shavon
by
6.0k points